Recruitment and selection of community health workers in Iran; a thematic analysis - Sareh Shakerian; Gozal Shafeei Gharanjik (BMC, 2023)
Abstract Background In Iran, community health workers (CHWs) are selected and employed according to the instructions of the Ministry of Health (MOH). The present study aimed to investigate the views of different stakeholders regarding the selection criteria, as well as the competency of CHWs. Methods This study was conducted using a qualitative thematic analysis in Golestan Province, Iran. Data were collected using semi-structured interviews with managers, supervisors, CHWs, and common people in 2021. The interviews were recorded and then transcribed. To extract key themes, the six-step Brown model was used, which involved becoming acquainted with the data, meaningful organization of transcripts, extracting primary open codes, searching for themes in an iterative approach, theme extraction, defining themes, and preparing a report. The relationships between codes and sub-themes and themes were represented using ATLAS.ti version 8. Results Data saturation was achieved after interviewing 22 people. The extracted data included 340 open codes, two main sub-themes of "CHW effectiveness" and "CHW sustainability", and three main themes of "criteria for employing competent people", "barriers to employing competent people", and "identifying the barriers to employing competent people", according to the MOH instructions. Conclusion In the present study, local hiring was one of the major challenges in the competency-based selection of CHWs. One of the most repeated codes was expanding the local hiring concept and its requirements. Since different regions of Iran have different climatic, economic, cultural, and social conditions, the selection and hiring criteria for CHWs should be tailored to the needs of the community.